Modulation analysis and optical solitons of perturbed nonlinear Schrödinger equation - Houwe, A.; Sabi’u, J.; Betchewe, G.; İnç, Mustafa; Doka, S.Y. (Sociedad Mexicana de Fisica, 2021)
We investigate modulation analysis and optical solitons of perturbed nonlinear Schrödinger equation (PNLSE). The PNLSE has terms of cubic nonlinearity and self-steepening and spatio-temporal dispersion (STD). Proposed model has been studied by [14, 15] without selfsteepening term. The presence of the STD can help to compensate the low GVD to the model. Bright and dark solitary waves, trigonometric, periodic and singular optical solitons are obtained by some expansion methods including exponential and sinh-Gordon. Obtained results will hold a significant place in the field of nonlinear optical fibers, where solitons are used to codify data. © 2021
Keywords: instability modulation; Optical soliton; perturbed nonlinear Schrödinger equation